2000
DOI: 10.1002/1521-3862(200008)6:4<185::aid-cvde185>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Gas-Phase FTIR Monitoring of MOCVD Processes: LaF3 Films Using the Second Generation La(hfac)3·diglyme Precursor

Abstract: In-situ gas-phase Fourier transform infrared spectroscopy (FTIR) studies of thermally activated processes occurring in the metal±organic chemical vapor deposition (MOCVD) of La(hfac) 3 ×diglyme provide evidence that the precursor can be evaporated from the melt up to 130 C without side decomposition processes. In contrast, under typical operating conditions in hot-wall MOCVD processes, the precursor undergoes different demolition pathways. Under Ar, it is stable up to 300 C. At higher temperatures, decompositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Malandrino et al 370 synthesized novel complex precursors Eu(hfac) 3 ·glyme (glyme = mono- or di-) and found that both complexes are thermally stable and could be evaporated with < 4% residue. Another study by this group 371 suggested that La(hfac) 3 ·diglyme could be evaporated from the melt up to 130 °C without side decomposition processes. The Malandrino group 372 further prepared and characterized Nd(hfac) 3 ·monoglyme·H 2 O and Nd(hfac) 3 ·diglyme, which exhibit high volatility and good thermal stability with a residue left lower than 3%.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Malandrino et al 370 synthesized novel complex precursors Eu(hfac) 3 ·glyme (glyme = mono- or di-) and found that both complexes are thermally stable and could be evaporated with < 4% residue. Another study by this group 371 suggested that La(hfac) 3 ·diglyme could be evaporated from the melt up to 130 °C without side decomposition processes. The Malandrino group 372 further prepared and characterized Nd(hfac) 3 ·monoglyme·H 2 O and Nd(hfac) 3 ·diglyme, which exhibit high volatility and good thermal stability with a residue left lower than 3%.…”
Section: Other Applicationsmentioning
confidence: 99%
“…[32] The way in which in-situ FTIR measurements assist in the understanding of mechanism pathways is shown in a recent paper dealing with La(hfac) 3 diglyme. [33] FTIR spectroscopy was successfully applied to technological-scale CVD systems, [34,35] and growth processes on fibers have been improved by in-situ monitoring. [36] The purpose of the present paper is to summarize the potential of FTIR spectroscopy in the analysis of the thermal behavior of compounds to be used as CVD precursors.…”
Section: Introductionmentioning
confidence: 99%
“…The AFM data indicate a very smooth surface with a root mean square (rms) roughness of 0.96 nm for films deposited at high temperature/high oxygen flow. [31] to the simple fluoride, [23,25,32] or oxyfluoride, phases. [26,27,33] In fact, the fluorinated nature of the b-diketonate moiety favors side reactions that yield fluoride or oxyfluoride 736…”
mentioning
confidence: 99%